Cathepsin H Is an Additional Convertase of Pro-granzyme B - D'Angelo, Michael E. (American Society for Biochemistry and Molecular Biology, 2010)
The serine protease granzyme B (GrB) is the most potent proapoptotic cytotoxin of the granule exocytosis pathway of cytotoxic lymphocytes. GrB is synthesized as a zymogen (proGrB) and activated in cytotoxic granules by the lysosomal cysteine protease cathepsin C (CatC) which removes the N-terminal dipeptide Gly-Glu. It has been shown recently that mice lacking CatC nonetheless express significant residual GrB activity, indicating the presence of additional proGrB convertases. Here, we describe an assay to assess activation of proGrB and show that the amino-peptidase cathepsin H (CatH) has proGrB convertase activity in vitro, whereas dipeptidylpeptidase II does not. We generated mice lacking both CatC and CatH expression (CatCH(−/−)) and found that their lymphocytes have reduced convertase activity compared with those from CatC-deficient mice. Despite this, cytotoxic lymphocytes from CatCH(−/−) mice retain cytotoxic activity and some residual GrB activity. We conclude that CatH can act as an additional proGrB convertase and that other protease/s (apart from dipeptidylpeptidase II) must also possess convertase activity. This indicates a great deal of functional redundancy in GrB maturation, which would prevent pathogen-mediated immune suppression by via convertase inhibition.